Dinamika Cyberbullying pada Remaja Indonesia: Tinjauan Literatur Naratif - Rahmania, Farra Anisa; Anisa, Syarifah Na’imi; Zhafira, Allia (Batanang : Jurnal Psikologi, 2025)
Cyberbullying has become increasingly common in line with the rapid advancement of digital technology and the extensive use of social media, especially among Indonesian adolescents. This study aims to identify the psychological and social factors associated with the emergence of cyberbullying behaviors among adolescents. The method used in this research is a narrative literature review of empirical studies published in reputable national and international journals between 2018 and 2023. The literature search conducted using the keywords cyberbullying, adolescent, and Indonesian participants, resulted in eight eligible articles, which were then analyzed qualitatively through narrative synthesis. The findings indicate that several variables consistently relate to cyberbullying, including intrapersonal factors (self-esteem, emotion regulation, empathy, and self-control), interpersonal factors (parent–child relationships, parenting style, and peer relationships), as well as personality and moral factors (dark triad personality traits and moral disengagement). Future research is expected to further explore additional variables that remain understudied and to integrate diverse findings to provide a more comprehensive understanding of cyberbullying dynamics among Indonesian adolescents.